Role of ascorbic acid as a seed priming agent in alleviating salt induced damages in germination and early seedling growth of rice (Oryza sativa L.): Ascorbic acid seed priming improves salt tolerance in rice - Akter, H; Akter, M; Ahmed, F; Helal, MG; Mahmud, JA (Bangladesh Journal of Agriculture, 2026)
Salinity is one of the major brutal abiotic stresses that affect crop productivity worldwide. Seed priming with different bio-regulators has emerged as an effective and practical approach to inducing the plant tolerance against different abiotic stress including salinity. Therefore a study was conducted at the Agroforestry Field Laboratory, Sher-e-Bangla Agricultural University, Dhaka during July 2022 to September 2022 to find out potential of seed priming with ascorbic acid inalleviation of germination and growth inhibition of rice (Oryza sativa L.) seedlings under salt stress. The study included four levels ascorbic acid viz. i) 0 mM (A0), ii) 0.125 mM (A1) iii) 0.250 mM (A2) iv) 0.5 mM (A3) for seed priming and four levels of salinity: i) 0 dS m-1 (S0), ii) 5 dS m-1(S1), iii) 10 dS m-1(S2), iv) 15 dS m-1 (S3) NaCl set up in petridishes and pots. Salinity levels significantly affected germination and growth attributes like germination percentage, germination speed, germination energy, radical length, plumule length, plant height, plant fresh weight, plant dry weight, SPAD value and leaf relative water content. However, ascorbic acid primed seeds provided higher germination percentage, germination speed, germination energy, radical length, plumule length, plant height, plant fresh weight, plant dry weight, SPAD value and leaf relative water content in contrast to respective salt stress. Among the doses of ascorbic acids 0.250 mM and 0.5 mM performed better than the 0.125 mM. Thus, this study suggests that use of ascorbic acid as a seed priming agent with appropriate dose can enhance the tolerance of rice seedlings against salt stress. Bangladesh J. Agri. 2025, 50(2): 85-102